APLIKASI PENDATAAN MAHASISWA PENERIMA BEASISWA BERBASIS WEB PADA FAKULTAS EKONOMI UNIVERSITAS PASIR PENGARAIAN - Jufri, Jufri; Devi, Kamala (Riau Journal Of Computer Science, 2019)
Scholarship data collection at the Faculty of Economics still uses a manual method that is all the data collection process is still input using Microsoft Excel. So that the scholarship data collection is not neatly arranged and not archived properly. This results in difficulties in finding data and requires a long time. Data archiving is more likely in the form of a document sheet (Hard File), therefore it is necessary to create a system that can help the Faculty of Economics in data collection of students who receive scholarships. After a series of testing of the scholarship recipient's data collection system can be implemented at the Faculty of Economics. Archiving data on scholarship recipient students is well archived, making it easier for users to search data from year to year according to study programs and scholarship programs that are archived in the data collection system and become more efficient